8 am versus 8 pm labour induction with dinoprostone vaginal tablets in term pregnancies with unfavourable cervices—a randomised controlled trial - Aizura Syafinaz Ahmad Adlan; Vikneswaran Virasamy; Doris Ng Sin-Wen; Noor Azmi Mat Adenan (Clinical and Experimental Obstetrics & Gynecology)
Background: To evaluate the feasibility of timing delivery of induction of labour cases to occur during office hours and reduce night time delivery. Methods: Patients scheduled for induction of labour were randomized to 8 am or 8 pm insertion of dinoprostone vaginal tablets. The main outcome measure was time of delivery between 8 am to 5 pm. The secondary outcome measures were mode of delivery and its indications, neonatal outcomes, maternal satisfaction and labour room staff satisfaction. Results: 164 patients were recruited with 78 patients randomized to the 8 am group and 86 patients randomized to the 8 pm group. There was no significant difference in timing of delivery between both groups, with delivery between 8 am to 5 pm for the 8 am group being 35.9% and for the 8 pm group being 44.2% (P = 0.339). For the secondary outcome measures, there was no significant difference found between mode of delivery (vaginal, instrumental or Caesarean section), neonatal Apgar score and cord blood pH, nor maternal satisfaction score based on the Likert scale. However there was a statistically significant difference (P = 0.001) for labour ward staff satisfaction based on the Likert scale, favouring the 8 pm induction timing. Conclusion: 8 am versus 8 pm timing for induction of labour has no significant difference to the timing of delivery during office hours, but the 8 pm induction of labour group has significantly greater labour ward staff satisfaction.